Sales Intern in SKOCH Group - Ulidra, Steven (ATLAS SkillTech University, 2024)
The sales internship presented challenges that honed my problem-solving skills. Whether it was navigating client expectations, meeting sales targets, or adapting to unforeseen market changes, each challenge became an opportunity to learn and innovate. The solutions devised during these instances showcased my ability to think critically and act decisively.
Project Report on Sales Intern in SKOCH Group (2022-24) Under the Guidance of Prof. Zuleika Homavazir
Keywords: problem-solving skills; navigating client expectations; market changes